EFEKTIVITAS MEDIASI DALAM PENCEGAHAN PERCERAIAN DI PENGADILAN AGAMA KELAS 1A KOTA BENGKULU - Wijaya, Agung Supra (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
Researcher discusses the problems effectiveness of mediation in Class 1A Religious Court of Bengkulu.  In the first study that has  been conducted by researchers at the  Class 1A Religious Court of Bengkulu  City found  information about  the low success of the mediation conducted by a judge mediator and the sheer  number divorce  cases in Class 1A Religious Court of Bengkulu.  Based on the description above,  the formulation of the problem: How is the effectiveness of mediation in preventing divorce conducted by the Religious Court of Bengkulu City Class 1A. And the factors that become supporting and inhibiting the success of mediation in Class 1A Religious Court of Bengkulu  City . In this thesis  the author uses  the method used  in the study of this law is the juridical sociological. Results from this study is the author  concluded that the mediation is conducted in the Religious Court of Bengkulu City Class 1A by following the reference of PERMA No.01 of 2008 has not been effective although there are successful but still very low, many factors are the cause of which is the level of compliance in the community through  the process of mediation is still very low, culture  of people who argue that divorce  is not a disgrace to individuals  and families and the quality of the judges  appointed as a mediator is still uneven and  there  are  only four (6) judges  who  have  attended mediation training organized by the  Supreme Court Republic  of Indonesia.